PENGGUNAAN METODE DRILL UNTUK MENINGKATKAN HASIL BELAJAR AKIDAH AKHLAK PESERTA DIDIK KELAS VII-A MTsN 4 SIDOARJO TAHUN PELAJARAN 2019-2020 - Nur Hidayati (Madaris: Jurnal Guru Inovatif, 2021)
The purpose of this study was to obtain a series of information / data about the Akidah Akhlak learning process which included: (1) Implementation of the use of the drill method for class VII-A students of MTsN 4 Sidoarjo, (2) The role of the drill method to improve the Akidah Akhlak learning activities of class students. VII-A MTsN 4 Sidoarjo, (3) The role of the drill method to improve the learning outcomes of students in class VII-A MTsN 4 Sidoarjo, (4) Students' responses to the use of the drill method in learning Akidah Akhlak. This type of research is a classroom action research conducted in four cycles. The subjects of this study were 34 students of class VII-A in semester II of the 2019-2020 school year. The data collected included, teacher and student activity data collected through observation using observation sheets, cognitive learning outcome data were collected using objective tests and student response data to the use of the drill method were collected using a questionnaire. The indicator of success in this study is if classically 85% of the students' learning outcomes test reaches a score of 75, according to the minimum completeness category (KKM) that applies at MTsN 4 Sidoarjo. Indicators of successful achievement of learning outcomes in the affective domain, if it reaches 80% of students reach the "good" category. Indicators of the success of students' responses to the use of the drill method, if 80% of students reach the "good" category, while for teacher activities it is said to be successful if they have carried out learning activities in the "very good" category. The results showed that (1) the learning that was carried out by the teacher could run very well, cyclically the results of the intervention in each cycle were used for the next cycle, and the deficiencies in each cycle could be corrected in the next cycle, (2) Observation of student activity for affective assessment increased, and has met the KKM. Thus the optimization of the use of the drill method can improve learning outcomes of Akidah Akhlak on the Basic Competence of understanding the material of Asmaul Husnah, (4) Students' responses to the use of the drill method used are considered very good on each indicator. Students become unsaturated, and it is easier to understand the material.